The Effectiveness of Audiovisual Media Health Education on Flood Disaster Preparedness in Elementary School Children - Siswi, Dinda; Setioputro, Baskoro; Wantiyah (Jurnal Kegawatdaruratan Medis Indonesia, 2023)
Flood disaster preparedness is necessary to provide information to reduce the impact of the disaster on human life and surroundings. This research aims to analyze the effectiveness of health education about flood disaster preparedness students at elementary school students. This research used pre-experimental designs with one group pretest-postest design type. The Sample in this study involved 20 students in 5th grade obtained with total sampling. The research instrument utilized a flood disaster preparedness questionnaire. Before being given health education, most students' knowledge was in ready and almost ready categories, with seven students for each level (35%). The result of the post-test showed that students' knowledge levels were at a very ready category of as many as five people (25%), ready level of as many as five people (25%), and almost ready as many as eight people (40%). This study concludes that there were differences in students' knowledge before and after being given health education (p: 0.032, α: 0.05). This show that health education on flood disaster preparedness through audiovisual media effectively increases the knowledge students of in elementary school. Therefore, audiovisual-based education can be used as an alternative medium to provide health education for students.